Exploring the causal relationship: bidirectional mendelian randomization study on benign prostatic hyperplasia and cardiovascular diseases - Xiang, Nanyan; Su, Shiqi; Wang, Zeng; Yang, Yong; Chen, Boxi; Shi, Rui; Zheng, Tao; Liao, Banghua; Lin, Yifei; Huang, Jin (Frontiers in Genetics, 2024)
BACKGROUND: Benign prostatic hyperplasia (BPH) is a common disease occurring in elderly and middle-aged men, and cardiovascular diseases (CVDs) areis one of the major causes of death worldwide. Many observational studies examined have found a strong association between BPH and CVDs, but the causal relationship between them is unclear. The aim of this study was to determine the causal relationship between BPH and CVDs, specifically five diseases: (five diseases including stroke, coronary heart disease (CHD), heart failure, myocardial infarction (MI), and atrial fibrillation (AF). METHODS: In this study, we obtained single nucleotide polymorphisms (SNPs) of patients with BPH from the UK Biobank database and patients with CVDs from the UK Biobank, the HERMES Consortium, and the FinnGen Genome Database, each used as a genetic tool for a mendelian randomization (MR) study. We used conventional MR analysis to assess potential causal direction between BPH and CVDs, as well as MR-Egger, MR using a Robust Adjusted Profile Score (MR-PRESSO), model-based estimation (MBE) and weighted median methods for sensitivity analysis. RESULTS: Using a bidirectional two-sample MR study, we found that BPH patients had an increased risk of developing CHD (ConMix OR = 1.152, 95% CI: 1.011-1.235, P = 0.035) and MI (ConMix OR = 1.107. 95% CI: 1.022-1.164, P = 0.013), but a decreased risk of stroke (ConMix OR = 0.872, 95% CI: 0.797-0.926, P = 0.002). The reverse study was not statistically significant and further research may be needed. CONCLUSIONS: Our study suggests a potential causal relationship between BPH and CVDs. BPH appears to be a risk factor for CHD and MI, but it may be protective against stroke. Our study suggested a potential causal relationship between BPH and CVDs. BPH appeared to be was a risk factor for CHD and MI, but was protective against stroke. There was no evidence of a causal association in the forward reverse study, and a larger sample size was needed in follow-up to further explore the potential association.